2018
DOI: 10.17221/147/2017-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative evaluation of Northern red oak (Quercus rubra L.) in arid areas of North-Western Bohemia

Abstract: The article analyses growth and quality of Northern red oak (Quercus rubra Linnaeus) based on 13 research plots (seven in red oak stands and six in sessile oak stands) with the ages between 17 to 159 years. The collected data includes height, DBH, crown diameter, stem and crown quality, health status of each tree on the plot. Analogous plots were chosen in sessile oak (Quercus sessilis Linnaeus) stands on similar sites to get reference data. The results proved the high wood production potential of red oak when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…The results also confirmed better production capacity of northern red oak crowns compared to durmast oak through crown volume, which was manifested in trees thicker than 27 cm. It can be assumed that it increases even in older age, which was also confirmed by the study of Kupka et al (2018). These authors also found out greater volume production per spatial unit (crown cover area), which was significantly greater compared to durmast oak.…”
Section: Qualitative Productionsupporting
confidence: 60%
See 4 more Smart Citations
“…The results also confirmed better production capacity of northern red oak crowns compared to durmast oak through crown volume, which was manifested in trees thicker than 27 cm. It can be assumed that it increases even in older age, which was also confirmed by the study of Kupka et al (2018). These authors also found out greater volume production per spatial unit (crown cover area), which was significantly greater compared to durmast oak.…”
Section: Qualitative Productionsupporting
confidence: 60%
“…It was usually planted in the group of forest types Carpineto-Quercetum, but Tokár (1985), for example, states that in the region of the Little Carpathians it was mostly planted in the group of forest types Corneto-Quercetum, at altitudes up to 200 m. In Bohemia, it was similar. There are data on its planting up to 300 m (Kupka et al 2018). In contrast, in Romania it was also planted at higher altitudes up to 780 m (Sandi & Nicolescu 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations